Konstruksi Genealogi Pemikiran Raghib al-Isfahani - Saifur Rahman (Palita: Journal of Social Religion Research, 2022)
A discourse needs to be exposed in order to know its deepest meaning and what variables are hidden behind it. That is what this research wants to present through genealogical theory. The material object is Raghib al-Isfahani's moral thought, which is quite unique, namely making the shari'ah conception as its center. This study will discuss two main things, namely, (1) how is the conception of sharia in Raghib al-Isfahani's moral thought; (2) how is the genealogical construction of Raghib al-Isfahani's moral thought. This research is a library research. Michel Foucault's theory is used as an analytical knife. The results state: first, the conception of shari'ah in Raghib's moral thought has expanded its meaning, namely ahkam al-syariah and makarim al-syariah. Ahkam al-Sharia gave birth to dogmatic moral behavior as well as being the foundation of Makarim al-Sharia. As for Makarim al-Shariah itself gave birth to ethical moral behavior. Second, the genealogical construction of Raghib's moral thought is formed from several factors, the existence of a power struggle that causes social disorder (social disorder), the supremacy of sharia in all fields carried out by the Bani Seljuq government, and the development of imamate discourse by the assassin extremism movement. Raghib's moral thought was to rehabilitate the behavior of the people at that time while at the same time stemming the influence of the priestly discourse which tended to be destructive.